Build Smart Home Controls Using Wemos Microcontroller-Based Telegram App - Freddy Artadima Silaban; Rendy Elmianto; Lukman Madriavin Silalahi (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
Current technological developments are very fast and progressing. One of the developments that occurs in the IoT (Internet Of Things) system. Many IOT (Internet Of Things) systems already have open source and can be suitable as needed, therefore by utilizing technological advancements, lamp controllers and house doors are made using Telegram applications. This control system can carry out home communications and control home electronic devices such as lights and house doors remotely using the Wemos and Arduino UNO microcontrollers. The Telegram application is used to send commands connected to the io.adafruit.com server. This system can provide notifications sent to the Telegram application when the house door is opened. The conclusion of the results obtained when the tool needed to communicate with the server is 12.94 seconds. For the voltage of 4 lights ± 220 V AC and for servo voltage ± 4.8 V DC. For the response time of the tool to the server ± 3 seconds, while the response time of the tool to Nextion LCD is ± 1 second